Effectiveness of Recruitment and Selection Practices in Public Sector Higher Education Institutions: Evidence from Ghana - Isaac Christopher Otoo; Juliet Assuming; Paul Mensah Agyei (European Scientific Journal, ESJ, 2018)
The purpose of this paper is to assess the recruitment and selection practices of public sector higher education institutions in Ghana. The research employed quantitative research approach with a descriptive survey design. Questionnaire was used to collect data from 128 respondents. Stratified and simple random sampling techniques were used to select the sample from the targeted population. Data processing was done using SPSS version 22. Results of the analyses showed, inter alia, the following; (a) Public sector higher education institutions in Ghana predominantly relies on recommendation as its main mode of employment; (b) Identification of available vacancies and delay in feedback after interviews were the two main challenges with the public sector higher education institutions in Ghana recruitment and selection practices. It is recommended that employee referrals (recommendation) though a good idea should be reduced, public sector higher education institutions in Ghana should make use of adverts (either print or electronic or both) in publicising its vacant positions.